Alts democratized : a practical guide to alternative mutual funds and ETFs for financial advisors - Rabe, Jessica Lynn (Wiley finance series, 2015)
A Comprehensive Review of the Liquid Alts Market and How '40 Act Products Can Enhance Client Portfolios Liquid alternatives give investors access to hedge fund strategies with the benefits of '40 Act products: lower fees, higher liquidity, greater transparency, and improved tax efficiency. Alts Democratized is a hands-on guide that offers financial advisors and individual investors the tools and analysis to enhance client portfolios using alternative mutual funds and ETFs. Well-grounded in research and replete with more than 100 exhibits of Lipper data, Alts Democratized profiles the top te.